2022
DOI: 10.3390/applmicrobiol2010017
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Lipase Production of Bacillus salmalaya Strain 139SI Using Different Carbon Sources and Surfactants

Abstract: Microbial lipase is one of the major sources of the enzyme that has been broadly exploited in the food, detergent, and pharmaceutical industries due to its high catalytic activity, high yield, and environmental friendliness and cost-effectiveness. Therefore, the aim of this study was to optimize the medium for the submerged fermentation for lipase production by a novel strain, Bacillus salmalaya strain 139SI. The media subjected to lipase production was Luria Bertani (LB) with different carbon sources and surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…The auto-aggregation property of bacterial isolates allows them to adhere to the epithelial lining of intestines, which is considered as a beneficial property because it prevents the flush out of bacterial strains from the body through peristalsis. The auto-aggregation percentages of isolated strains increased with time which is consistent with previous findings [49,50]. In a study conducted by Abid et al, it was revealed that Lactobacilli strains, i.e., NMCC-14, exhibit the highest auto-aggregation properties, i.e., 47.55 ± 0.08.…”
Section: Discussionsupporting
confidence: 89%
“…The auto-aggregation property of bacterial isolates allows them to adhere to the epithelial lining of intestines, which is considered as a beneficial property because it prevents the flush out of bacterial strains from the body through peristalsis. The auto-aggregation percentages of isolated strains increased with time which is consistent with previous findings [49,50]. In a study conducted by Abid et al, it was revealed that Lactobacilli strains, i.e., NMCC-14, exhibit the highest auto-aggregation properties, i.e., 47.55 ± 0.08.…”
Section: Discussionsupporting
confidence: 89%
“…gessardii [59], and B. subtilis [47] maximally secreted lipolytic enzyme when the production media were constituted with tween 80, olive oil, palm oil, beef tallow, and waste cooking oil, respectively. Among the surfactants, tween 80, which showed the maximum inducible effect in the present study, has been reported to be a potent lipase inducer compared to tween 20, sodium dodecyl sulfate and triton X-100 [60].…”
Section: Discussionmentioning
confidence: 51%
“…Fe-MIL-88NH 2 was prepared according to the previously reported protocol [39]. Briefly, FeCl 3 •6H 2 O (0.187 g; 0.692 mmol) and 2-aminoterephthalicacid (0.126 g; 0.692 mmol) were dissolved in 15 mL of DMF followed by the addition of 3.45 mmol of acetic acid into the resulting mixture.…”
Section: Methodsmentioning
confidence: 99%